Syntactic Category of Determiners in Georgian and Mingrelian (Combining Descriptive rules of Georgian Traditional Grammar and Formal of Generative Grammar) - Gogia, Tamar ("Intercultural Dialogues" Transactions, 2023)
Georgian and Mingrelian are both considered to be languages without determiners. The paper seeks to identify determiners in these languages based on descriptive rules of the Georgian traditional grammar (GTG), on the one hand, and descriptive and formal rules of generative grammar, on the other. The research question is, which grammatical units have the syntactic function of the determiners in Georgian and Mignrelian? We hypothesize that one of the subgroups of attributive modifiers defined in GTG has the same syntactic characteristics as determiners in the determiner phase (DP) hypothesis. This subgroup is so-called “modifiers functionally equalized with adjectives” within GTG. Based on the combination of descriptive rules of Georgian traditional grammar and descriptive and formal rules of generative grammar (X’ schema and PD hypothesis), we created two tests for identifying determiners in the languages under analysis. We analyzed corpus examples of the determiner (DP) / noun phrases (NP), constructed syntactic trees, and identified projection levels and structural relations of their constituents. We examined the same corpus data using the above-mentioned tests for identifying determiners. Based on the analysis we concluded that so-called “modifiers functionally equalized with adjectives” are determiners in Georgian and Mingrelian.